Body fat, physical activity, and dietary patterns of adolescents in a mountainous region of Santa Catarina state, Brazil - Adair da Silva Lopes; Edson Machado de Arruda (Universidade Federal de Santa Catarina, 2007)
The objective of the present study was to analyze the body fat, physical activity, and dietary patterns of male adolescents in a mountainous region of Santa Catarina state, Brazil. The subjects were 1,024 adolescents, 10 to 17 years old, from public and private schools. The sample was selected by a three-stage cluster sampling method, where the laststage sampling units were entire classes. The prevalence of overweight and obesity was determined considering body fat level estimated using predictive equations. Physical activity and food intake were assessed using a questionnaire. Statistical analyses included: descriptive statistics, Chi-square test, and one-way ANOVA with Scheffé post hoc multiple comparisons. It was observed that 25.6% of the adolescents were overweight or obese and 29.4% were physically inactive. Regardingdietary patterns, subjects reported the following consumption levels of sugars and fats: soft drinks (36.9%), sweets (41.3%), and fries (29.1%). In general, there were no differences in activity patterns, diet, or body fatness between age groups (10-17years). Adolescents enrolled at private schools exhibited higher body fatness (p<.001), less physical activity (p<.05), poorer dietary habits (high consumption of fries, soft drinks, sweets, high fat foods, and low consumption of vegetables; p<.05) than adolescents at public schools. Approximately one in four adolescents in the mountainous region exhibited excess body fat and insufficient physical activity. Poor dietary habits were observed in one out of three adolescents. In general, adolescent students at private schools had more body fat, less activity, and poorer dietary habits than those attending public schools. RESUMO O objetivo do presente estudo foi analisar a gordura corporal, o nível de atividade física e hábitos alimentares de adolescentes do Município de Lages, Região Serrana do Estado de Santa Catarina, Brasil. A amostra, constituída de 1024 adolescentes do sexo masculino (10 a 17 anos), foi selecionada de forma aleatória simples quanto às escolas, conglomerada por sala de aula e estratifi cada por rede de ensino. A gordura corporal foi estimada por meio de equações preditivas do percentual de gordura. O nível de atividade física e os hábitos alimentares foram coletados por meio de umquestionário. Na análise dos dados, utilizou-se a estatística descritiva, teste do Qui-quadrado, análise de variância (ANOVA) one-way e o teste de Scheffé (p<0,05). Os resultados evidenciaram que 25,6% dos adolescentes apresentaram excesso de gordura corporal e 29,4% foram considerados insufi cientemente ativos. Dentre os hábitos alimentares inadequados, destacaram-se: o consumo excessivo de refrigerantes (36,9%), doces (41,3%) e frituras (29,1%). De modo geral, o nívelde atividade física, os hábitos alimentares e a gordura corporal não diferiram em relação às idades (p>0,05). Os escolares da rede particular apresentaram mais gordura corporal (p<0,001), baixos níveis de atividade física (p<0,05) e hábitosalimentares menos saudáveis do que os da rede pública (p<0,05). Pode-se concluir que, aproximadamente, um em cada quatro adolescentes da região serrana apresentou excesso de gordura corporal e níveis insufi cientes de atividade física;um em cada três apresentou hábitos alimentares pouco saudáveis. Os adolescentes da rede particular apresentaram mais gordura corporal, baixos níveis de atividade física e piores hábitos alimentares do que os da rede pública.